M1 and M2 Monocytes in Rheumatoid Arthritis: A Contribution of Imbalance of M1/M2 Monocytes to Osteoclastogenesis - Fukui, Shoichi; Iwamoto, Naoki; Takatani, Ayuko; Igawa, Takashi; Shimizu, Toshimasa; Umeda, Masataka; Nishino, Ayako; Horai, Yoshiro; Hirai, Yasuko; Koga, Tomohiro; Kawashiri, Shin-ya; Tamai, Mami; et al. (Frontiers in Immunology, 2018)
Objectives We investigated the relationships among M1 monocytes, M2 monocytes, osteoclast (OC) differentiation ability, and clinical characteristics in patients with rheumatoid arthritis (RA). Methods Peripheral blood mononuclear cells (PBMCs) were isolated from RA patients and healthy donors, and we then investigated the number of M1 monocytes or M2 monocytes by fluorescence-activated cell sorting. We also obtained and cultured CD14-positive cells from PBMCs from RA patients and healthy donors to investigate OC differentiation in vitro. Results Forty RA patients and 20 healthy donors were included. Twenty-two patients (55%) were anticitrullinated protein antibody (ACPA) positive. The median M1/M2 ratio was 0.59 (0.31–1.11, interquartile range). There were no significant differences between the RA patients and healthy donors. There was a positive correlation between the M1/M2 ratio and the differentiated OC number in vitro in RA patients (ρ = 0.81, p < 0.001). The ACPA-positive patients had significantly higher M1/M2 ratios in vivo (p = 0.028) and significantly greater numbers of OCs in vitro (p = 0.005) than the ACPA-negative patients. Multivariable regression analysis revealed that the M1/M2 ratio was the sole significant contribution factor to in vitro osteoclastogenesis. RA patients with M1/M2 ratios >1 (having relatively more M1 monocytes) had higher C-reactive protein and erythrocyte sedimentation rates than RA patients with M1/M2 ratios ≤1. M1-dominant monocytes in vitro produced higher concentrations of interleukin-6 upon stimulation with lipopolysaccharide than M2 monocytes. Conclusion M1/M2 monocytes imbalance strongly contributes to osteoclastogenesis of RA patients. Our findings cast M1 and M2 monocyte subsets in a new light as a new target of treatments for RA to prevent progression of osteoclastic bone destruction.